Polychaete meets octopus: symbiotic relationship between Spathochaeta octopodis gen. et sp. nov. (Annelida: Chrysopetalidae) and Octopus sp. (Mollusca: Octopodidae). Issue 1 (2nd January 2019) - Jimi, Naoto; Moritaki, Takeya; Kajihara, Hiroshi
Abstract : Marine annelids in the subfamily Calamyzinae (family Chrysopetalidae) are either symbiotic or free-living forms that have been mainly reported from deep-sea chemosynthetic systems. Symbiotic calamyzines mainly live in the mantle cavity of bivalves in hydrothermal vents or cold seeps, but one species is also found to be inserted into the epidermis of polychaetes. We found a single specimen of calamyzine polychaete on the body surface of Octopus sp. collected in the Sea of Kumano (Japan), which represents the first known record of symbiotic association between polychaetes and octopuses. We described the specimen as Spathochaeta octopodis gen. et sp. nov. Spathochaeta gen. nov. can be discriminated from other genera in Calamyzinae by the presence of spatula-shaped notochaetae and dorsal chaetal lobes. We also provided the phylogenetic position of S. octopodis gen. et sp. nov. within Chrysopetalidae based on four gene markers (COI, 16S, 18S, H3). www.zoobank.org/urn:lsid:zoobank.org:pub:A8FB15C1-31A7-4487-966B-13F10E19A373.